Principios teóricos da etnografía da comunicación. Consideracións xerais para unha análise aplicada ao contexto galego1 - Gestido de la Torre, Eloi (Madrygal. Revista de Estudios Gallegos, 2005)
This paper presents several thinkings about a specific theory and method of interactional analysis. From the fieldof the Ethnography of Communication, we try to recover, review and present the theoretical rudiments proposed by Dell Hymes since 1962 in order to prove their application within the concrete analysis field of Galician speech events.
Keywords: Sociolinguistics; comunication ethnography; conversation; interation; speaking model; comunicative situations and events; coloquial language